Exploring the Link Between Eating Habits, Sleep Quality, and Toddler Growth Through Path Analysis - Dian Ayu Pramukawati; Rita Benya Adriani; Bhisma Murti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In 2023, it was recorded that 56.7% of children aged 0-59 months in Indonesia experienced growth that did not meet age standards. This study aims to explore the combined effects of eating habits and sleep quality on the growth of children aged 36-59 months. A total of 230 children from early childhood education (ECE) centres were analyzed using path analysis. The findings indicate that longer meal duration and picky eating habits directly influence children's growth, while emotional undereating, distractions during meals, and sleep quality have an indirect effect. The results emphasize the importance of healthy eating patterns and quality sleep for toddler development. Parents can positively contribute to their children's health by promoting balanced diets and consistent sleep routines. Parents and caregivers can establish regular mealtimes, reduce distractions during meals, and encourage consistent sleep schedules by understanding the impact of eating and sleeping habits.